Rancang Bangun Pengaduk Manual Pada Digester Biogas Kotoran Sapi untuk Meningkatkan Pembentukan Gas Metana - Candra Tri Kurniawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to design, build and increase methane gas levels in a biogas digester based on a manual stirrer. Where so far biogas materials still use natural secaera fermentation without human help. The initial stage of making this biogas material stirrer control tool is by looking at the original form of processing biogas material. In the biogas processing building, there are three important parts in biogas processing, namely the inlet (this place is used to mix a mixture of manure and water into the digester), the digester (also called the reactor functions as a place to process cow dung through a process of fermentation by bacteria to produce gas) and outlet (this channel is used to remove impurities that have been fermented by bacteria. This channel works on the principle of hydrostatic pressure equilibrium). It is in this part of the inlet that there is a mixing device. The tool is used to prepare a good mixture of water and animal feces. This manual stirring device is made of several important components, namely such as the propeller blade, the core iron and the stirring handle which uses the manual working principle. The presence of this tool can help increase methane gas formation in the biogas digester